Função afim y = ax + b , sabendo que f(1) = 5 e f(-2) = -4
Soluções para a tarefa
Respondido por
16
f(1)=5
y= a+b
a+b=5
-2a+b=-4x(-1)
-------------
a+b=5
2a-b=4
------------
3a=9
a=9/3
a=3
a+b=5
3+b=5
b=5-3
b=2
---------
y=3x+2
y= a+b
a+b=5
-2a+b=-4x(-1)
-------------
a+b=5
2a-b=4
------------
3a=9
a=9/3
a=3
a+b=5
3+b=5
b=5-3
b=2
---------
y=3x+2
Respondido por
5
Resolução:
Dados:
Y = ax + b f(1 ) = 5
f(-2) = - 4
![f(1) = 5 f(1) = 5](https://tex.z-dn.net/?f=f%281%29+%3D+5)
![ax+b=y ax+b=y](https://tex.z-dn.net/?f=ax%2Bb%3Dy)
ou ![a+b=5 a+b=5](https://tex.z-dn.net/?f=a%2Bb%3D5)
![f(-2)=-4 f(-2)=-4](https://tex.z-dn.net/?f=f%28-2%29%3D-4)
![ax+b=y ax+b=y](https://tex.z-dn.net/?f=ax%2Bb%3Dy)
ou ![-2a+b=-4 -2a+b=-4](https://tex.z-dn.net/?f=-2a%2Bb%3D-4)
![\left \{ {{a+b=5} \atop {-2a+b=-4}} \right. \left \{ {{a+b=5} \atop {-2a+b=-4}} \right.](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Ba%2Bb%3D5%7D+%5Catop+%7B-2a%2Bb%3D-4%7D%7D+%5Cright.+)
![\left \{ {{a+b=5.(2)} \atop {-2a+b=-4}} \right. \left \{ {{a+b=5.(2)} \atop {-2a+b=-4}} \right.](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Ba%2Bb%3D5.%282%29%7D+%5Catop+%7B-2a%2Bb%3D-4%7D%7D+%5Cright.+)
2a + 2b = 10
-2a + b = -4 +
--------------------
0 + 3b = 6
b = 6 / 3
b = 2
a + b = 5
a + 2 = 5
a = 5 - 2
a = 3
portanto;
y = ax + b com a = 3 e b = 2
y = 3x + 2 ou f (x) = 3x + 2
bons estudos:
Dados:
Y = ax + b f(1 ) = 5
f(-2) = - 4
2a + 2b = 10
-2a + b = -4 +
--------------------
0 + 3b = 6
b = 6 / 3
b = 2
a + b = 5
a + 2 = 5
a = 5 - 2
a = 3
portanto;
y = ax + b com a = 3 e b = 2
y = 3x + 2 ou f (x) = 3x + 2
bons estudos:
Perguntas interessantes
História,
11 meses atrás
Química,
11 meses atrás
Ed. Física,
11 meses atrás
Contabilidade,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás